(untitled) - José L. Herrera-Elizondo; Diego García-Compean; Raúl A. Jiménez-Castillo; Fernando García-Villarreal; María F. Castillo-Martínez; Grecia C. Celis-Valenzuela; Sofía Rodríguez-Jacobo; Paola J. Bran-Alvarado; Omar D. Borjas-Almaguer; Héctor J. Maldonado-Garza; Joel O. Jáquez-Quintana; José A. González-González (Permanyer, 2022)
Introduction and objectives: The adenoma detection rate (ADR) is defined as the presence of at least 1 adenoma in patients ≥ 50 years on a screening colonoscopy. This becomes important due to the association of adenomas and colorectal cancer. It is recommended to have an ADR of 25% in men and women ≥ 50 years. Our goal was to know the ADR of gastroenterology fellows versus attending physicians. Materials and methods: We performed an observational, descriptive, and retrospective study where we reviewed medical records of patients who underwent a colonoscopy in the period of 2 years. Demographic, clinical data and the ADR of fellows and attending physicians were analyzed. Results: We evaluate 363 procedures: Fellows performed 279 and attending physicians performed 84. Polyps were found in 112 patients, and the mean age was 58 years (17-90). The ADR for men and women ≥ 50 years for fellows and attending physicians was 23% versus 31.7% (p = 0.18) respectively. Conclusion: Gastroenterology fellows achieved an ADR slightly below the international standards, with an ADR of 23% among men and women ≥ 50 years, compared to 31.7% of attending physicians.